Main complications of diabetic patients May-December 2020 IESS Guaranda hospital (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2021)
The patent ductus arteriosus (DAP) is the congenital heart disease that occurs most frequently in newborns, generating a significant short circuit that generally needs its interruption by drug administration; in the country it is estimated that about 2,500 children are born each year with congenital heart defects.General purpose: To determine the efficacy of pharmacological closure of persistent ductus arteriosus in neonates at the Francisco Icaza Bustamante Hospital between 2016-2019. Materials and methods: This are a descriptive, quantitative and descriptive investigation of retrospective analytical cross-section.Results: Of 199 neonatal patients taken with a diagnosis of DAP, 82% (163 patients) were successful in closing the ductus with drugs vs. 18% (36 patients) without success in pharmacological closure; 169 neonates (84%) were treated with paracetamol versus 30 patients (15%) who were treated with ibuprofen; Drug-associated complications occurred in 18% (36 patients).Conclusions: Having carried out and completed this investigation, it is shown that the pharmacological treatment for persistent ductus arteriosus is highly effective, with paracetamol being the most widely used drug at present and with a minimal rate of complications.
Keywords: Patent ductus arteriosus; patent canal arteriosus; congenital heart disease; neonates; pharmacological treatment